2023
DOI: 10.7554/elife.69611
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the influences of sequence and position on yeast uORF activity using massively parallel reporter systems and machine learning

Abstract: Upstream open reading frames (uORFs) are potent cis-acting regulators of mRNA translation and nonsense-mediated decay (NMD). While both AUG- and non-AUG initiated uORFs are ubiquitous in ribosome profiling studies, few uORFs have been experimentally tested. Consequently, the relative influences of sequence, structural, and positional features on uORF activity have not been determined. We quantified thousands of yeast uORFs using massively parallel reporter assays in wildtype and ∆upf1 yeast. While nearly all A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Previous studies reached different conclusions concerning the impact of IF uAUGs on translation [15, 20, 27, 28]. To clarify this, we determined the relationship between the location of OOF and IF uAUGs in the 5’UTR and the translation output of the mRNAs, in both yeast and human sequences, synthetic or endogenous.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies reached different conclusions concerning the impact of IF uAUGs on translation [15, 20, 27, 28]. To clarify this, we determined the relationship between the location of OOF and IF uAUGs in the 5’UTR and the translation output of the mRNAs, in both yeast and human sequences, synthetic or endogenous.…”
Section: Resultsmentioning
confidence: 97%
“…Hence, we examined our profiling data more closely to determine if eIF2A might affect the translation of mRNAs harboring uORFs in yeast cells. We did not restrict our attention to stimulatory uORFs, which are rare in yeast ( May et al, 2023 ), but included all uORFs in our analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published research has identified potential uORFs upstream of several genes that are amplified by CNVs in one or more strains, including GAP1 , DAL80 , and UTH1 (Zhang and Dietrich 2005; Cvijović et al 2007; Spealman et al 2018; May et al 2023). Using ribosome profiling data from each strain we manually identified potential uORFs in 49 of the 109 CNV amplified genes.…”
Section: Resultsmentioning
confidence: 99%
“…Because uORFs have been known to play a role in translational regulation we sought to determine if previously identified uORF may be present in our data. We calculated the mean TL length of genes containing either ‘predicted’ uORFs from (Spealman et al 2018) or ‘validated’ uORFs from (May et al 2023). Because of the validation methodology used in (May et al 2023), uORFs greater than 180bp distance from the main ORF TIS were not tested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation